2017
DOI: 10.1080/02699931.2017.1356700
|View full text |Cite
|
Sign up to set email alerts
|

Be aware of the rifle but do not forget the stench: differential effects of fear and disgust on lexical processing and memory

Abstract: The aim of this study was to investigate the role of discrete emotions in lexical processing and memory, focusing on disgust and fear. We compared neutral words to disgust-related words and fear-related words in three experiments. In Experiments 1 and 2, participants performed a lexical decision task (LDT), and in Experiment 3 an affective categorisation task. These tasks were followed by an unexpected memory task. The results of the LDT experiments showed slower reaction times for both types of negative words… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 44 publications
3
30
2
Order By: Relevance
“…Two sets of 12 disgusting words and two sets of 12 neutral words were selected from two normative studies containing ratings for five discrete emotions (Ferré et al, 2017 ; Hinojosa et al, 2016 ) and used as auditory distractors in the oddball task, and as targets and foils in a subsequent surprise recognition task. The disgusting and neutral words were matched with respect to familiarity, imageability, concreteness, age of acquisition, word frequency (log value), number of letters, number of syllables, number of lexical neighbors, high frequency neighbors, mean Levenshtein distance of the 20 closest words, contextual diversity (log value), bigram frequency, and trigram frequency.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two sets of 12 disgusting words and two sets of 12 neutral words were selected from two normative studies containing ratings for five discrete emotions (Ferré et al, 2017 ; Hinojosa et al, 2016 ) and used as auditory distractors in the oddball task, and as targets and foils in a subsequent surprise recognition task. The disgusting and neutral words were matched with respect to familiarity, imageability, concreteness, age of acquisition, word frequency (log value), number of letters, number of syllables, number of lexical neighbors, high frequency neighbors, mean Levenshtein distance of the 20 closest words, contextual diversity (log value), bigram frequency, and trigram frequency.…”
Section: Methodsmentioning
confidence: 99%
“…In line with past work on the effect of deviant sounds, we predicted that both types of deviant stimuli would, by virtue of violating sensory predictions, yield longer response times than standard sounds. More importantly, based on the results of previous work suggesting that disgusting stimuli grab attention more than neutral stimuli, we predicted that, compared to neutral words, disgusting words should yield greater distraction in the cross-modal oddball task, and superior memory performance in the recognition task (Ferré et al, 2017). Furthermore, these specific effects of disgusting words should increase with the participants' individual sensitivity to disgust, a prediction we assessed by measuring the correlation between performance in the cross-modal oddball and recognition tasks on the one hand, and the participants' score on a disgust sensitivity scale on the other.…”
Section: The Present Studymentioning
confidence: 97%
See 1 more Smart Citation
“…It has been suggested that people might be aversive to imagining disgusting words because of their strong negative connotations (Thibodeau, 2016). Indeed, words eliciting disgust showed consistent processing disadvantage (Briesemeister, Kuchinke, & Jacobs, 2011; Ferré, Haro, & Hinojosa, 2018). Taking into account that food-wasting behavior was considered mostly morally disgusting, its ratings of imageability might be lowered because of its moral association with disgusting behavior.…”
Section: Discussionmentioning
confidence: 99%
“…No differences between disgust-and fear-related word pairs were found for these factors. A recent study attributed the higher level of free recall for disgust-related than neutral and fear-related words to deeper elaborative encoding 42 . Since the nature of our task (creating common mental representations of word pairs) forced elaborative processing for all the experimental conditions, it should eliminate also such differences.…”
Section: Differences In Memory Modulation By Disgust and Fearmentioning
confidence: 98%